Emerging non-13-valent pneumococcal conjugate vaccine (PCV13) serotypes causing adult invasive pneumococcal disease in the late-PCV13 period in Spain. (June 2020) - González-Díaz, A.; Càmara, J.; Ercibengoa, M.; Cercenado, E.; Larrosa, N.; Quesada, M.D.; Fontanals, D.; Cubero, M.; Marimón, J.M.; Yuste, J.; Ardanuy, C.
Abstract: Objective: An early reduction of adult invasive pneumococcal disease (IPD) was observed after the 13-valent pneumococcal conjugate vaccine (PCV13) introduction for children in Spain. We analysed the epidemiology of adult IPD in the late-PCV13 period. Methods: This was a prospective multicentre study of adult IPD involving six hospitals. Strains were serotyped, genotyped and studied for antimicrobial susceptibility. The late-PCV13 period was compared with the pre- and early-PCV13 periods. Results: A total of 2197 episodes were collected—949 in 2008–2009, 609 in 2012–2013 and 639 in 2015–2016. The initial decrease of IPD observed (from 12.3/100 000 to 8.1/100 000; 2008–2009 versus 2012–2013) plateaued in 2015–2016 (8.3/100 000). IPD due to PCV13 serotypes decreased (from 7.7 to 3.5 to 2.3/100 000; p < 0.05), whereas IPD caused by non-PCV13 serotypes increased (from 4.5 to 4.6 to 6.0/100 000; p < 0.05). The most frequent serotypes in the late-PCV13 period were: 8 (15.1%), 3 (10.5%), 12F (7.9%) and 9N (5.4%). These serotypes were related to major genotypes: CC53 (59.8%) and CC404 (30.4%) for serotype 8, CC180 (64.1%) and CC260 (28.1%) for serotype 3, CC989 (91.7%) for serotype 12F and CC67 (84.8%) for serotype 9N. Penicillin-non-susceptibility (21.2%) was associated with serotypes 11A (CC156), 14 (CC156) and 19A (CC320), and macrolide-resistance was related to serotypes 24F and 19A. Rates of pneumococcal meningitis remained stable throughout the periods (ranges 0.9, 0.8 and 1.0/100 000). Conclusions: The initial decrease of adult IPD observed after PCV13 introduction for children has been balanced by the rise of non-PCV13 serotypes. The spread of antibiotic-resistant lineages related to non-PCV13 serotypes (11A and 24F) could be a threat for the treatment of serious pneumococcal diseases.